Permanenter Notstand und der Kampf um gute Sorge(arbeit) – Polanyi’sche Doppelbewegungen in der Marktgesellschaft - Décieux, Fabienne; Becker, Karina; Kutlu, Yalcin (Industrielle Beziehungen, 2020)
Der Artikel untersucht kollektives Interessenhandeln in der (Klein-)Kinderbetreuung in Deutschland und Österreich. Mit der Polanyi’schen Figur der Doppelbewegung werden die Dynamiken der aktuellen Aushandlungen im Feld der Sorge und Sorgearbeit aufeinander bezogen und analytisch gefasst. Die Bewegung in Form einer (Quasi-)Vermarktlichung steht im Spannungsverhältnis zum ausgeprägten Berufsethos der ErzieherInnen, um das sie durch Proteste (Österreich) und Streiks (Deutschland) kämpfen.
Keywords: (Early) Child care; (Klein-)Kinderbetreuung; (Quasi-)Vermarktlichung; (quasi) marketization; D63; Industrial Relations. JEL: B54; Industrielle Beziehungen; J81; Polanyi; Sorgearbeit; care work

Karl Polanyi - The Life and Works of an Epochal Thinker - Thurnher, Armin; Aulenbacher, Brigitte; Novy, Andreas; Marterbauer, Markus; Polanyi Levitt, Kari (2020)
On 8 May 2018, the International Karl Polanyi Society was founded in Vienna. This marked the beginning of a new phase of engagement with a thinker who had already come to be regarded as a centennial figure in the Anglo-Saxon world. This book serves as an introduction to The Great Transformation, Polanyi’s magnum opus and one of the most important works of the 20th century. It helps us to understand the background to Karl Polanyi’s intellectual career, sketches the lives of his family members, describes the milieus of Budapest, Vienna, London and New York, which were such informative influences in his life, and sheds light on his relationship with contemporaries such as Keynes, Mises and Hayek. Renowned Polanyi researchers, including, most notably his daughter Kari Polanyi Levitt, elucidate Polanyian concepts such as ‘fictitious commodities’ and apply his analysis to an era when everything seems to be subjected to the mechanics of the market.
Keywords: Great Transformation, The (Book); fictitious commodities